Optimaslisasi Hasil Belajar Siswa Pada Pembelajaran PAI Menggunakan Metode Make A Match Kelas IV SDN 02 Durian Tinggi - Sri Dewi Mulyani; Leni Marsanti; Sasri Wahyuni; Roza Elfira; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in the material Emulating Asmaul Husna by applying the make a match learning method in class IV with the variables that are the target of change in this study are learning outcomes, while the action variables used in this study are the make a match learning method. This research is classroom action research carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementation/action, observation/observation, and reflection The data collection techniques used are observation/observation, interviews, documents and tests. Based on the results of the study, it can be concluded that student learning outcomes continue to increase until they reach a significant increase. Student learning outcomes at the pre-action stage were 30%, in cycle I (first) increased to 60%, in cycle II (second) also increased to 90%. Thus, a recommendation can be submitted that the application of the make a match learning method can improve student learning outcomes in the material Emulating Asmaul Husna for the 2024/2025 Academic Year.